STUDY ON SOME HEAMATOLOGICAL CHANGES IN CYPRINUS CARPIO ( L. ) FISH AFTER EXPOSURE TO DIFFERENT CONCENTRATIONS OF SUMCIDIN FENVALERATE ( 20% ) PESTICIDE - AL-ALI, M.F.; BNAY, M.A.A.; ALZOBAIDY, A.M.H. (Iraqi Journal of Aquaculture, 2022)
C. carpio fish was exposed to different concentrations of sumcidin pesticide ( 0.005 , 0.05 and 0.5 ) mg \ l . All treatment fish was showed oscillation in rates some of hematological parameters in present study compared with control fish . Red and white cells , hemoglobin , P.C.V. , M.C.V. and M.C.H.C. were showed decrease in their rates averages in treated fish compared with control , abnormality shapes in red blood cells in exposure fish to Sumciden pesticide observed compared with control .